REINSTATING FUNCTIONALISM IN THE FIGURATIONAL APPROACH TO ORGANIZATIONS - Šņitņikovs, Aleksejs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Over the past two decades, there have been attempts to apply ideas from figurational sociology founded by Norbert Elias in research of different aspects of organizational life. The central contributions are derived from his theory of the civilizing process and the principles of process sociology. While this research mostly is relevant for contemporary organization theory, many contributions tend to emphasize Elias’s relational approach to the neglect of his functionalism, which underlies the whole corpus of Elias’s works. Rediscovery of Elias’s functionalism opens up the way for a fruitful reinterpretation of the central concept of his sociology, figuration, and enables to find new ways of combining figurational sociology with more familiar approaches to organization theory, in particular, with contingency theory. This helps to identify the factor of technology in the theory of the civilizing process and place it in the context of the concepts of figurational sociology such as interdependence, power and subjectivity, which enhances the analytical strength of figurational approach to organizations. The paper discusses some applications of figurational sociology to date and points to new directions in the study of organizations with the use of the conceptual tools of figurational approach.